ANALISIS MINAT BELI KONSUMEN MUSLIM TERHADAP PRODUK YANG TIDAK DIPERPANJANG SERTIFIKAT HALALNYA - Anggit Listyoningrum; Albari Albari (Faculty of Economics, Universitas Islam Indonesia, 2012)
This research is aim to analysize the influence of attitude, subjective norm, and control behavior perception to consumer purchase interest based on Ajsenâ's Theory of Planned Behavior ( 1991). Object of this research was a cake product of a company which no longer has halal certificate from Majelis Ulama Indonesia (MUI). As many as 100 students of Fakultas Ekonomi UII were taken as respondents by using judgment sampling method. These respondents are assumed to represent muslim consumers of the cake product. A multiple regression model was run to examine the influence of independent variables to dependent variable. The result shows the positive influence of all independent variables to consumer purchase interest variable.